The Discourse of Muhammadiyah and Nahdlatul Ulama with Considerations of Geertz’s Religion of Java - Firdaus Wajdi (Universitas Negeri Jakarta, 2018)
Muhammadiyah and Nahdlatul Ulama are two biggest Muslim organizations in the most populous Muslim country, Indonesia. Many studies have conducted to identify both roles in the Indonesian Islam context. However, there is lack study which actually traces possible similarities between the two. This paper illustrates the distinct description of the two organizations from the perspective of Clifford Geertz in his prominent work, the Religion of Java, where it covered some characteristics of the followers of both Muhammadiyah and Nahdlatul Ulama. This study then continues with possible similar identification of Muhammadiyah and Nahdlatul Ulama. This is qualitative study conducted through library research. This study concludes that despite the fact the differences, there are some similarities, which put the two organization together to contribute even more to the development of Islam in Indonesia. It then expects that the followers of both could work together to build peaceful Indonesian through better understanding of religious institutions such as the Muhammadiyah and Nahdlatul Ulama.